2018
DOI: 10.1002/ange.201711023
|View full text |Cite
|
Sign up to set email alerts
|

Erfassung der Humanexposition mit organischen Verbindungen in Innenraumumgebungen

Abstract: Die Rolle von Chemikalien in Innenraumumgebungen ist seit langem Gegenstand der Forschung. Die meisten der potenziellen Zielsubstanzen sind leichtflüchtige, flüchtige und schwerflüchtige organische Verbindungen (VVOCs, VOCs und SVOCs). In Abhängigkeit von ihren physikalischen Eigenschaften und Stoffübergangsbedingungen verteilen sie sich in oder zwischen der Gasphase, der Partikelphase, dem Hausstaub, Oberflächenfilmen, der Kleidung und anderen Textilien sowie Haut und Haaren der Bewohner. Demzufolge müssen In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 356 publications
(259 reference statements)
0
11
0
Order By: Relevance
“…Due to the sophisticated sampling and analysis, the portion of microplastics is usually not identified, but many additives in microplastics have been routinely recorded using house dust analysis and biomonitoring. [15] In one house dust sample, the sum of five identified types of microplastics was around 10 μg mg À 1 (1 %) (see Figure 1), but this result cannot be regarded as representative. Zhu et al [69] studied different indoor environments and found that residential apartments had the highest abundance of MPs in indoor dust samples.…”
Section: Indoor Exposure To Microplasticsmentioning
confidence: 94%
See 3 more Smart Citations
“…Due to the sophisticated sampling and analysis, the portion of microplastics is usually not identified, but many additives in microplastics have been routinely recorded using house dust analysis and biomonitoring. [15] In one house dust sample, the sum of five identified types of microplastics was around 10 μg mg À 1 (1 %) (see Figure 1), but this result cannot be regarded as representative. Zhu et al [69] studied different indoor environments and found that residential apartments had the highest abundance of MPs in indoor dust samples.…”
Section: Indoor Exposure To Microplasticsmentioning
confidence: 94%
“…Moreover, "intake" is in no way equal to "uptake". [15] However, when looking at the results shown in Table 4 and also taking into account related monomers and additives, one can certainly see a potential problem. It is therefore advisable to investigate the health effects of exposure to microplastics in a timely manner and in detail.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, "intake" is in no way equal to "uptake". [15] However, when looking at the results shown in Table 4 and also taking into account related monomers and additives, one can certainly see a potential problem. It is therefore advisable to investigate the health effects of…”
Section: Future Perspectivesmentioning
confidence: 99%